Blockage of indoleamine 2,3-dioxygenase regulates Japanese encephalitis via enhancement of type I/II IFN innate and adaptive T-cell responses - Kim, Seong Bum (J Neuroinflammation, 2016)
BACKGROUND: Japanese encephalitis (JE), a leading cause of viral encephalitis, is characterized by extensive neuroinflammation following infection with neurotropic JE virus (JEV). Indoleamine 2,3-dioxygenase (IDO) has been identified as an enzyme associated with immunoregulatory function. Although the regulatory role of IDO in viral replication has been postulated, the in vivo role of IDO activity has not been fully addressed in neurotropic virus-caused encephalitis. METHODS: Mice in which IDO activity was inhibited by genetic ablation or using a specific inhibitor were examined for mortality and clinical signs after infection. Neuroinflammation was evaluated by central nervous system (CNS) infiltration of leukocytes and cytokine expression. IDO expression, viral burden, JEV-specific T-cell, and type I/II interferon (IFN-I/II) innate responses were also analyzed. RESULTS: Elevated expression of IDO activity in myeloid and neuron cells of the lymphoid and CNS tissues was closely associated with clinical signs of JE. Furthermore, inhibition of IDO activity enhanced resistance to JE, reduced the viral burden in lymphoid and CNS tissues, and resulted in early and increased CNS infiltration by Ly-6C(hi) monocytes, NK, CD4(+), and CD8(+) T-cells. JE amelioration in IDO-ablated mice was also associated with enhanced NK and JEV-specific T-cell responses. More interestingly, IDO ablation induced rapid enhancement of type I IFN (IFN-I) innate responses in CD11c(+) dendritic cells (DCs), including conventional and plasmacytoid DCs, following JEV infection. This enhanced IFN-I innate response in IDO-ablated CD11c(+) DCs was coupled with strong induction of PRRs (RIG-I, MDA5), transcription factors (IRF7, STAT1), and antiviral ISG genes (Mx1, Mx2, ISG49, ISG54, ISG56). IDO ablation also enhanced the IFN-I innate response in neuron cells, which may delay the spread of virus in the CNS. Finally, we identified that IDO ablation in myeloid cells derived from hematopoietic stem cells (HSCs) dominantly contributed to JE amelioration and that HSC-derived leukocytes played a key role in the enhanced IFN-I innate responses in the IDO-ablated environment. CONCLUSIONS: Inhibition of IDO activity ameliorated JE via enhancement of antiviral IFN-I/II innate and adaptive T-cell responses and increased CNS infiltration of peripheral leukocytes. Therefore, our data provide valuable insight into the use of IDO inhibition by specific inhibitors as a promising tool for therapeutic and prophylactic strategies against viral encephalitis caused by neurotropic viruses.